1989
DOI: 10.1111/j.1365-2621.1989.tb03116.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microbiological Quality of Some Gamma Irradiated Indian Spices

Abstract: MATERIALS & METHODSIrradiated (10 kGy) and unirradiated pre-packed whole and ground spices including black pepper, red chilli, and turmeric were examined by six different laboratories for microbiological quality. No colony forming units (CFU) were reported in the largest quantity of irradiated spices used in the study by three out of six laboratories. The other three laboratories reported counts ranging between O-90 CFU/g in irradiated samples. None of the six laboratories reported the presence of E. coli or B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…Because the effect of Ethylene oxide on spore is not as big as for vegetable cells (Pafumi, 1986). Studies have suggested that gamma irradiation is the most effective and safe method for decontamination of spices and herbs (Pafumi, 1986;Sharma et al, 1989). Since the toxigenity of B. cereus has been proven, potential health hazards of foods containing spices and herbs contaminated with this bacterium should not be ignored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the effect of Ethylene oxide on spore is not as big as for vegetable cells (Pafumi, 1986). Studies have suggested that gamma irradiation is the most effective and safe method for decontamination of spices and herbs (Pafumi, 1986;Sharma et al, 1989). Since the toxigenity of B. cereus has been proven, potential health hazards of foods containing spices and herbs contaminated with this bacterium should not be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Spores survived because of inadequate heat treatment of food, can germinate when proper conditions is available (Aksu, 1994;Hefnawy et al, 1984;Konuma et al, 1988;Mosso et al, 1989;Pafumi, 1986;Powers et al, 1975). Microbiological safety of spices and herbs may be provided by several fumigation practices (ethylene oxide, propylene oxide), filtration, microwave treatment, ultra-violet irradiation, infra-red irradiation and gamma irradiation (Powers et al, 1975;Pruthi, 1980;Sharma et al, 1989). Heat treatment of raw spices is not recommended, because it often alters the aromatic and flavour components and colour characteristics (Pafumi, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The application of a 5 kGy dose was enough to reduce the microbial contamination to non-detectable levels. In addition, this dose assures the destruction of insects accidentally present in dry onion, in any developmental stage (Sharma, Padwal-Desai, & Nair, 1989).…”
Section: Sanitizing Evect Of the Gamma Radiationmentioning
confidence: 99%
“…In some countries, such as Australia and USA, up to 30-kGy dose is permitted. Irradiation at 10 kGy was found to be effective in destroying bacteria and moulds without affecting the quality attributes of different spices (Farag, Aziz, & Attia, 1995;Munasiri et al, 1987;Onyenekwe & Ogbadu, 1995;Sharma, Padwal-Desai, & Nair, 1989).…”
Section: Introductionmentioning
confidence: 98%